Abdominal Aortic Aneurysm With Renal Arteries Originating Above the Superior Mesenteric Artery. (January 2017) - Rao, Ajit; Korayem, Adam; Tadros, Rami; Faries, Peter; Marin, Michael; Chander, Rajiv
A 63-year-old female presented to clinic following an incidental finding of an abdominal aortic aneurysm (AAA). Preoperative imaging was consistent with an infrarenal AAA over 5-cm in diameter with both renal arteries originating above the superior mesenteric artery (SMA). The patient subsequently underwent an endovascular aneurysm repair (EVAR) using the AFX stent-graft (Endologix, Inc, Irvine, Calif). Notably, the proximal stent-graft piece was unsheathed with the image intensifier in a lateral position to ensure deployment below the SMA. Postoperative course was unremarkable and the patient is currently recovering well.